2017
DOI: 10.1111/ddi.12568
|View full text |Cite
|
Sign up to set email alerts
|

From insinuator to dominator: Foraging switching by an exotic ant

Abstract: Aim: Understanding the ecological conditions that determine invasive success requires information on the ecological dynamics in both the native and introduced range of exotic species. While numerous studies of the little fire ant, Wasmannia auropunctata, have focused on the evolutionary aspects of invasiveness, we know little about possible ecological dynamics that might contribute to the remarkable invasiveness of this species.Location: We investigate the ecological differences in resource discovery and recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…and C. picipes pilosulus , would be in the subordinate category too, although their behavior would be better interpreted as that of an insinuator species ( sensu Wilson, 1971). Insinuators arrive in small numbers and discretely steal food ( see Yitbarek, Vandermeer & Perfecto, 2017). What about the cold-climate specialist Formica spp.…”
Section: Discussionmentioning
confidence: 99%
“…and C. picipes pilosulus , would be in the subordinate category too, although their behavior would be better interpreted as that of an insinuator species ( sensu Wilson, 1971). Insinuators arrive in small numbers and discretely steal food ( see Yitbarek, Vandermeer & Perfecto, 2017). What about the cold-climate specialist Formica spp.…”
Section: Discussionmentioning
confidence: 99%
“…Wasmannia ants and brood were collected by scraping epiphytes and bark from trees and from hollowed out branches collected from the ground. Although Wasmannia ants in the area of the study may exist in large “supercolonies” spread out across farms (Yitbarek et al, 2017 ), we attempted to collect from different areas separated by at least 2 m for each replicate. All ants were kept in containers in the laboratory until the morning of experimental trials, but no longer than 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory experiments involving W. auropunctata and native ant species, showed that W. auropunctata had the poorest foraging abilities in terms of resources discovery(Vonshak et al 2012). In previous work, we compared competitive trade-offs and found that W. auropunctata was less efficient in discovering and recruiting worker to baits in their introduced habitat of Puerto Rico relative to their native habitat in Mexico, suggesting that competitive trade-offs are not indicative of invasive success(Yitbarek, Vandermeer & Perfecto 2017).The organization of exotic species within local species assemblages in their native ranges allows us to understand why some exotic species thrive in their introduced ranges(Calcaterra et al 2016). Here we sought to understand how W. auropunctata ranks relatively to locally dominant native ant species.…”
mentioning
confidence: 88%